2018
DOI: 10.1016/j.bpsc.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography Source Functional Connectivity Reveals Abnormal High-Frequency Communication Among Large-Scale Functional Networks in Depression

Abstract: These findings extend our understanding of the neurophysiological basis of abnormal resting-state functional connectivity in MDD and indicate that elevations in high-frequency DMN-FPN connectivity may be a neural marker linked to a more recurrent illness course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 70 publications
1
73
0
Order By: Relevance
“…The solution space consists of 6239 cortical gray matter voxels with a spatial resolution of 5 x 5 x 5 mm in a realistic head model. eLORETA is a suitable tool to investigate network activity and connectivity (Neuner et al, 2014;Thatcher et al, 2014;Liu et al, 2017;Samogin et al, 2019) and has provided important network insights into psychiatric disorders (Whitton et al, 2018;Imperatori et al, 2019;Samogin et al, 2019).…”
Section: Exact Low-resolution Electromagnetic Tomography (Eloreta)mentioning
confidence: 99%
“…The solution space consists of 6239 cortical gray matter voxels with a spatial resolution of 5 x 5 x 5 mm in a realistic head model. eLORETA is a suitable tool to investigate network activity and connectivity (Neuner et al, 2014;Thatcher et al, 2014;Liu et al, 2017;Samogin et al, 2019) and has provided important network insights into psychiatric disorders (Whitton et al, 2018;Imperatori et al, 2019;Samogin et al, 2019).…”
Section: Exact Low-resolution Electromagnetic Tomography (Eloreta)mentioning
confidence: 99%
“…Our human brain is considered as an integrated network, which consists of anatomically separated but functionally linked brain regions (van den Heuvel and Hulshoff Pol, 2010 ). Many studies using the fMRI technique reveal that the pathophysiology of MDD involves a large-scale dysfunction in functional brain networks (Kaiser et al, 2015 ; Lv et al, 2016 ; Williams, 2017 ; Whitton et al, 2018 ). The functional connectivity (FC) is used as a most common measure for exploring the functional brain networks.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, hyperconnectivity within the DMN could account for the maladaptive depressive rumination and the excessive self‐focus processing (Broyd et al, ; Hamilton et al, ; Holtzheimer & Mayberg, ). Hyperconnectivity between the DMN and the FPN regions may be more associated with impairments in goal‐directed behavior which is biased towards internal self‐referential thoughts (Kaiser, Andrews‐Hanna, Wager, & Pizzagalli, ; Whitton et al, ). Furthermore, Grimm et al (, ) associated increased self‐focus with the cortical midline structures (CMS), and Northoff et al showed an association between increased self‐focus and the CMS when clinically depressed (Northoff, , ; Northoff, Wiebking, Feinberg, & Panksepp, ).…”
Section: Discussionmentioning
confidence: 99%